Relationship between tethered swimming and undulatory underwater swimming performance - Ruiz-Navarro, J. J.; López-Belmonte, Ó.; Gay, A.; Cuenca-Fernández, F.; Arellano, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
With the exception of the dive, the underwater phase of the start and turns represent the fastest part of the freestyle, butterfly, and backstroke events, making undulatory underwater swimming (UUS) one of the most influential technical components on race performance (Mason & Cossor, 2000). Therefore, coaches should consider that any improvements within the underwater phase would lead to an enhancement of the start and turn performances, having a crucial impact on the overall race success. The UUS is a legdominated technique that achieves propulsion by performing body undulations while keeping a streamlined body position with the arms extended and held together over the head (Ruiz-Navarro et al., 2022a). The enhancement of UUS velocity could be achieved by either increasing propulsive forces or decreasing the active drag experienced. Hence, to understand the impact of the training and the development of this movement, it is crucial to conduct evaluations that allow for further insights. The analysis of propulsion in UUS has relied mainly on the analysis of vortex, visualizing and measuring the form, size, and velocity of the vortices generated by the body during the UUS through particle image velocimetry (PIV)(Arellano et al., 2002). Although PIV provides very useful information, requires deep knowledge and time to conduct the analysis. On the other hand, other methods have been applied in swimming literature to assess propulsive force in swimming strokes. For instance, the direct measurement of force in swimming stroke has been obtained through tethered means. Tethered swimming allows the measurement of exerted forces assessing individual forcetimes curves during the exercise. Consequently, its use improves the possibility of analysis and comparison of swimming technique profiles, showing positive correlation between tethered variables and swimming performance, especially in short distances (Morouço et al., 2011). Despite the use of tethered swimming in the four swimming strokes (Morouço et al., 2011) and its association, especially with short distance swimming performance (Ruiz-Navarro et al., 2020) its use has been never applied to UUS. Thus, to have a more practical way to assess UUS propulsive forces, this research aimed to study the relationship between tethered swimming and UUS performance. Our hypothesis was that UUS performance would be associated with tethered swimming variables in both sexes.